Firm-Level Evidence on International Stock Market Comovement - Robin Brooks; Marco Del Negro (Kiel Institute for World Economics (IfW), 2005)
We explore the link between international stock market comovement and the degree to which firms operate globally. Using stock returns and balance sheet data for companies in 20 countries, we estimate a factor model that decomposes stock returns into global, country-specific and industry-specific shocks. We find a large and highly significant link: on average, a firm raising its international sales by 10 percent raises the exposure of its stock return to global shocks by 2 percent and reduces its exposure to countryspecific shocks by 1.5 percent. This link has grown stronger since the mid-1980s.
Keywords: G15; G11; 330; Diversification; risk; international financial markets; industrial structure; Internationaler Finanzmarkt; Kapitalertrag; Portfolio-Management; Portfolio-Investition; Internationaler Preiszusammenhang; Globalisierung; Welt